INTELLIGENT DIAGNOSTIC SYSTEM OF EMERGENCY SITUATIONS IN TRACTION SUBSTATIONS DC - Nasyrov, Sh. N. (Science and Transport Progress, 2009)
In the article the architecture and algorithm of operating an expert system providing the efficiency of functioning the electric equipment for traction substation as well as the four-parameter belonging function are determined.